Evaluating coastal lagoon sustainability through the driver-pressure-state-impact-response approach: a study of Khenifiss Lagoon, southern Morocco - El Behja, Hamza; El M’rini, Abdelmounim; Nachite, Driss; Bouchkara, Mohammed; El Khalidi, Khalid; Zourarah, Bendahhou; Uddin, Md Galal; Abioui, Mohamed (Frontiers in Earth Science, 2024)
Coastal lagoons are valuable ecosystems, providing socioeconomic benefits and supporting human populations and biodiversity. However, these systems face several challenges, making them vulnerable to both natural and human factors. In this study, we apply the Driver-Pressure-State-Impact-Response (DPSIR) Approach to conduct a comprehensive socioeconomic and environmental assessment of the Khenifiss Lagoon to promote sustainable development and support decision-makers. Located on the southern Atlantic coast of Morocco, the lagoon was designated a natural reserve in 1962, a biological reserve in 1983, and a protected wetland under the Ramsar Convention since 1980. This study represents the initial endeavor to conduct a comprehensive global and multidisciplinary environmental assessment of the lagoon by using a wide range of data sources, including relevant publications and reports, satellite images and remote sensing data, field observations, and interviews, all analyzed under the DPSIR framework. Our findings show that both natural and human factors have an impact on the ecosystem. Natural Factors associated with the geomorphological features of the region likely contribute to the silting of the lagoon, possibly intensified by a large shipwreck stuck at its inlet. Meanwhile, human factors encompass population growth (at a rate of 2% per year), tourism, shellfish farming, fishing, shellfish harvesting, and salt extraction. Our results reveal significant changes in the lagoon’s condition in recent years, including a reduction in water body extent, a probable decrease in depth, and an increase in the accumulation of solid waste, plastics, and wastewater in three sectors spanning a total surface area of 464 ha (equivalent to 7% of the lagoon), a substantial expansion of the salt mining area encompassing 368 ha, and a remarkable loss of biodiversity, manifested in declining fish stocks and seabird populations. This study showed that the lagoon is positioned as a potential site for economic growth and serves to alert stakeholders and the local population to the ecosystem’s environmental issues. Based on the findings of this study, we highly recommend regulating human activities within the lagoon, the removal of the wreck at the entrance, proper waste management, community awareness programs, and strict monitoring and enforcement of regulations to protect the environment.